Aghrāḍu “Yā” al Nidā’i fī Sūrati al A’rāfi wa Hūd (Dirāsatun Taḥlīliyyatun Balāghiyyatun fī ‘ilmi al Ma’āniy) - Mangsur, Jadub; Ardabli, Aziz (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
Al-qu'an is the first source of Islamic law، which is obligatory for all muslims to do. To understand the Qur'an، it is necessary to master the sciences of Arabic، especially balaghah، among them the objectives of Nida'. In the Qur'an there is a lot of Nida' in which there is the meaning of qiyasi،which has been mentioned in the balaghah books. To know the purpose of the verse contained the letter Nida' ، the author did a study with the title "Yaa" Nida' in the letter al-a'raaf and hud (Study analysis balaghah in science ma' ani). And whosoever is in the heavens and the earth، he is the All-mighty، the All-wise. The purpose of this study is to find out what the purpose of "Yes" Nida' is in the letter al-a'raaf and hud is reviewed from the balaghah aspect. The objects in this study are surah al-a'raaf and hud. The data sources used in this study are primary and secondary sources. And the method of data collection that the authors use is library research by collecting primary and skunder data with methods of analyzing and reading books related to this research. And in this study the authors used descriptive analysis and content analysis using tables. The purpose of "Yaa" Nida' in surah al-a'raaf and hud varies in purpose and meaning، namely regret، herdik، spirit، amazement، relief، moaning